2018
DOI: 10.1073/pnas.1717295115
|View full text |Cite
|
Sign up to set email alerts
|

Global increase and geographic convergence in antibiotic consumption between 2000 and 2015

Abstract: SignificanceAntibiotic resistance, driven by antibiotic consumption, is a growing global health threat. Our report on antibiotic use in 76 countries over 16 years provides an up-to-date comprehensive assessment of global trends in antibiotic consumption. We find that the antibiotic consumption rate in low- and middle-income countries (LMICs) has been converging to (and in some countries surpassing) levels typically observed in high-income countries. However, inequities in drug access persist, as many LMICs con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

27
1,510
4
48

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 2,370 publications
(1,731 citation statements)
references
References 43 publications
27
1,510
4
48
Order By: Relevance
“…A previous study reported that the increase in global consumption of antibiotics was primarily due to increased antibiotic consumption in low- and middle-income countries (LMICs) [12]. Complex interactions exist between the levels of economic well-being [4], and inequities in drug access persist because many LMICs continue to be burdened with high rates of infectious disease-related mortality and low rates of antibiotic consumption [12]. Therefore, policy interventions in China should be made in consideration of unbalanced regional development and the consequences this may have on antibiotic consumption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study reported that the increase in global consumption of antibiotics was primarily due to increased antibiotic consumption in low- and middle-income countries (LMICs) [12]. Complex interactions exist between the levels of economic well-being [4], and inequities in drug access persist because many LMICs continue to be burdened with high rates of infectious disease-related mortality and low rates of antibiotic consumption [12]. Therefore, policy interventions in China should be made in consideration of unbalanced regional development and the consequences this may have on antibiotic consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Among Chinese inpatients, 70 out of 100 are using antibiotics [11], which is a significant problem: the maximum rate of inpatient antibiotic usage set by the World Health Organization (WHO) is 30%. Between 2000 and 2015, antibiotic consumption in China increased at a growth rate of 82.6%, from 2.3 to 4.2 billion accumulative defined daily doses (DDDs) [12]. Additionally, as antibiotic prophylaxis effectively prevents postoperative wound infections, antibiotics are widely used in surgery [13].…”
Section: Introductionmentioning
confidence: 99%
“…The global antibiotic consumption data (2000–15) for 76 countries show that Pakistan is among the leading LMIC consumers of antibiotics, where the consumption has increased by 65% from 0.8 to 1.3 billion daily defined doses (DDDs) . This is also evident from the national pharmaceutical sales data in Pakistan, which correlate with antibiotic consumption in the country.…”
Section: Introductionmentioning
confidence: 95%
“…As most antibiotics are prescribed in primary care and many of these prescriptions for mainly lower respiratory tract infections (LRTI) such as acute bronchitis is of questionable value, reducing inappropriate prescribing in this setting is paramount . Spain is one of the countries with the highest antibiotic prescribing, observing a slight increase over the last years . Several strategies have been developed to reduce unnecessary antibiotic prescribing in the community with little success, but in general, interventions based on multiple initiatives have been found to be more effective than those focused on only one initiative.…”
Section: Introductionmentioning
confidence: 99%